SAT0159 Non-vertebral fractures and its associates in female rheumatoid arthritis (ra) patients: the oslo, truro, and amsterdam (ostra) collaborative study. (1st June 2001) - Haugeberg, G; Lodder, M; Lems, W; Ørstavik, R; Dijkmans, B; Kvien, T; Woolf, A
Abstract : Background: Objectives: To examine non-vertebral fractures (N-VF) in RA patients, of similar age, disease duration and rheumatoid factor status recruited from three European countries, and their association with bone mineral density (BMD), demographic and disease related associates. Methods: 150 (50 from each country) consecutive female RA patients (ACR 1987 criteria, disease duration > 5 yrs, age 50–70 yrs) visiting the out-patient Department of Rheumatology in the participating centres were included. Data on N-VF occurring after age 25 and after RA diagnosis, demographics and measures of disease activity were collected. Dual energy X-ray absorptiometry (DXA) was used to measure femoral neck and spine L2–4 BMD adjusted for age, weight and height. BMD was expressed in g/cm 2 . To investigate associations between history of N-VF and disease related variables, we used bi-variate (Students t-test, Pearson Chi square test) and multivariate statistical analyses (logistic regression). Results: A total of 25 patients (Oslo 11, Truro 1 and Amsterdam 13 patients) reported a history of previous N-VF (total number of fractures 34). In the Truro patients BMD (adjusted for age, weight and height) in both spine and hip was higher than in Oslo and Amsterdam patients. A statistical difference between those with and without a previous N-VF was found for the variables (mean (SD)) listed in the Table 1 and for disease duration (22.6 vs. 16.6 yrs, p = 0.01). BMD in the femoral neck but not in the spine was independently associated with a history of a N-VF after adjusting for age, weight, height, disease duration and Larsen score using logistic regression. Conclusion: Our cross sectional findings indicate that BMD is a risk factor for N-VF in female RA patients. Weather this concerns a causal relationship needs confirmation in prospective studies.